Japanese Commons in the Coastal Seas How the Satoumi Concept Harmonizes Human Activity in Coastal Seas with High Productivity and Diversity - Yanagi, Tetsuo. (Springer Japan : Imprint: Springer, 2013)
The author proposed the satoumi concept, analogous to the satoyama concept on land, as coastal sea with high biodiversity and productivity in harmony with human interaction in 1998. The concept for environmental conservation in the coastal seas has been widely accepted and was included in the Japanese national policy of Strategy for Establishment of an Environmental Nation in 2007. This book is a translation of the authors Japanese book (2010) in response to concerns and questions about satoumi, including: Does biodiversity increase as a result of human interaction in coastal seas? Do the economics of fishing villages need to be considered in detail? What legal support is necessary for the creation of satoumi? Is there a relation between the concepts of God and Nature in satoumi? What is the relationship between fishermen and city dwellers? Chapter 1 presents the basic concept of satoumi. In Chapter 2 the relation between biodiversity and human interaction, economic problems related to satoumi, legal support for satoumi creation, satoumi from the point of view of landscape ecology, and the relation between society and science with regard to the satoumi movement are discussed. In Chapter 3 examples of satoumi creation in Japan are presented, andin Chapter 4 the overseas dissemination of the satoumi concept is introduced, with Chapter 5 providing the conclusion.